Goals and goal setting desktop learning for busy professionals (Menlo Park, Calif. : Crisp Learning, 2001)
This self-directed learning package help users to identify the differences between a mission, goal and objective,understand the role of management in setting goals and recognize opportunities for goals.
System requirements : Windows 95 or later or Windows NT 4 or later ; Pentium (90MHz or faster) ; 3 MB fess ; 16 MB memory(RAM) ; 2x or faster CD-ROM; 800 x 600 monitor resolution; browser software such as Internet Explorer or Netscape Navigator.
Keywords: Goal setting in personnel management; Supervision